Methods of Organizing Recreational Zones in the Quarry Areas Located on the Banks of the Chirchik River (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, the main ecological methods of improving the reclamation condition of the quarry were considered. The current state of the Chirchik river quarry in Tashkent, Uzbekistan was studied. The negative impact of the situation on ecology has been determined. Proposals for the use of vertical greening methods have been presented to eliminate the identified negative deficiencies.